Interpersonal Functions of Discourse Text in Chinese Ethnics, Medan, Indonesia - Tien Rafida (Budapest International Research and Critics University, 2018)
Chinese people as the focus of this research is a tribal group originated from China and settles in the city of Medan. Discourse text of Chinese young generation in Medan show unfamiliar theme as the most theme appeared in the clause. The appearance of familiar theme based on presence of modus, that is declarative modus, interrogative, and imperative, thus otherwise for unfamiliar theme. Therefore, using unfamiliar theme in discourse text of young generation give indication that young generation want the delivery of first message based on the important things and not based on standard structure of sentences, for example SPOK (subject, predicate, object, and adverb).